Prevalence and use of services in persons with schizophrenia and related disorders in Málaga (Spain) - Moreno-Kustner, Berta; Martín, Carlos; Mayoral Cleries, Fermín; Angona, Pedro; García-Herrera, José María; Navas Campaña, Desirée María; Rivas, Fabio (My University, 2013)
Background/Objectives Very few studies have examined schizophrenia morbidity in Spain, using multiple sources of information. We performed a 1-year prevalence study of schizophrenia and related disorders in Málaga and the use of services in a population aged 14 years or older living in the mental health catchment area of Carlos Haya hospital (Málaga, Spain). Methods Data were obtained from multiple sources of information mainly clinical databases. We selected more than 4000 persons as “possible cases” and we consult case notes and key informant (general practice and psychiatrists) to confirm schizophrenic diagnoses and place of living. Results A total of 1808 patients, 1169 men and 639 women were included as cases in the study. The one year ICD-10 prevalence rate was 6,8 (6,5-7,1) per 1000 adult population. Almost 80% of cases were in contact with public mental health services. Responsibility for schizophrenic patients is mainly carried by mental health services. Discussion/Conclusion Health planning should be based on local data about prevalence and use of services. Multiple sources of information are essential for accurate estimation of prevalence of schizophrenia disorders. Grants
Keywords: Psicología; Esquizofrenia; Prevalence; Schizophrenia; Epidemiology; Use of services